Midazolam with meperidine and dexmedetomidine vs. midazolam with meperidine for sedation during ERCP: prospective, randomized, double-blinded trial - Lee, Ban Seok; Ryu, Junghee; Lee, Sang Hyub; Lee, Min Geun; Jang, Sang Eon; Hwang, Jin-Hyeok; Ryu, Ji Kon; Do, Sang-Hwan; Kim, Yong-Tae (Endoscopy, 2014)
Background and study aim: The combination of midazolam and opioid has been widely used as a standard sedative regimen for endoscopic retrograde cholangiopancreatography (ERCP). Following recent evidence that dexmedetomidine may exert a synergistic effect in combination with midazolam, this study compared the sedative effect and adverse events of midazolam – meperidine – dexmedetomidine (MMD) and midazolam – meperidine during ERCP.Patients and methods: A total of 110 patients who were scheduled for ERCP were prospectively enrolled and randomly assigned, in a double-blind manner, to the MMD (n = 53) or midazolam – meperidine (n = 57) groups. Each patient received an intravenous (IV) bolus dose of midazolam and meperidine (0.06 mg/kg and 50 mg, 30 % reduction and 25 mg for patients aged ≥ 65 years, respectively). To this dose, a continuous IV infusion of dexmedetomidine (1 μg/kg/h; MMD group) or the same volume of normal saline (midazolam – meperidine group) was added. The sedation level (Ramsay Sedation Scale [RSS]) as well as hemodynamic and respiratory changes were assessed.Results: Adequate sedation (RSS ≥ 3) was maintained during ERCP in 75.5 % and 36.8 % of the MMD and midazolam – meperidine group, respectively (P < 0.001). RSS scores were significantly higher in the MMD group (P < 0.001). Intraoperative bispectral index scores were significantly lower in the MMD group (P < 0.001) than in the midazolam – meperidine group. Lower additional (P = 0.001) and total (P = 0.003) doses of midazolam were required in the MMD group. Patients in the MMD group showed lower pain scores (P < 0.001) and higher satisfaction scores (P < 0.001). Desaturation occurred more frequently in the midazolam – meperidine group (11 vs. 1; P = 0.003).Conclusions: The addition of dexmedetomidine to the midazolam – meperidine regimen provided better sedative efficacy and a superior safety profile during ERCP compared with a midazolam – meperidine regimen.This trial was registered at ClinicalTrials.gov Identifier (NCT01404689).